Quality and Performance Measurement in Primary Diabetes Care: A Qualitative Study in Urban China - Alon Rasooly; Yancen Pan; Zhenqing Tang; He Jiangjiang; Moriah E. Ellen; Orly Manor; Shanlian Hu; Nadav Davidovitch (Kerman University of Medical Sciences, 2022)
Background  Quality measurements in primary healthcare (PHC) have become an essential component for improving diabetes outcomes in many high-income countries. However, little is known about their implementation within the Chinese health-system context and how they are perceived by patients, physicians, and policy-makers. We examined stakeholders' perceptions of quality and performance measurements for primary diabetes care in Shanghai, China, and analyzed facilitators and barriers to implementation.Methods  In-depth interviews with 26 key stakeholders were conducted from 2018 to 2019. Participants were sampled from two hospitals, four community healthcare centers (CHCs), and four institutes involved in regulating CHCs. The Consolidated Framework for Implementation Research (CFIR) guided data analysis.Results  Existing quality measurements were uniformly implemented via a top-down process, with daily monitoring of family doctors' work and pay-for-performance incentives. Barriers included excluding frontline clinicians from indicator planning, a lack of transparent reporting, and a rigid organizational culture with limited bottom-up feedback. Findings under the CFIR construct "organizational incentives" suggested that current pay-for-performance incentives function as a "double-edged sword," increasing family doctors' motivation to excel while creating pressures to "game the system" among some physicians. When considering the CFIR construct "reflecting and evaluating," policy-makers perceived the online evaluation application - which provides daily reports on family doctors' work - to be an essential tool for improving quality; however, this information was not visible to patients. Findings included under the "network and communication" construct showed that specialists support the work of family doctors by providing training and patient consultations in CHCs.Conclusion  The quality of healthcare could be considerably enhanced by involving patients and physicians in decisions on quality measurement. Strengthening hospital-community partnerships can improve the quality of primary care in hospital-centric systems. The case of Shanghai provides compelling policy lessons for other health systems faced with the challenge of improving PHC.